Age related changes in basal concentrations of FSH, LH and testosterone in indigenous and crossbred bovine males - S K RAJAK; A KUMARESAN; S NAYAK; S CHHILLAR; N M ATTUPURAM; M K MUHAMMAD ASLAM; R K BAITHALU; T K MOHANTY (Indian Journal of Animal Sciences, 2016)
Collectively, the findings of the present study revealed that the concentrations of both FSH and LH were highest at 18 months of age in crossbred males, while in indigenous males, the FSH and LH concentrations were highest at 18 and 24 month of age, respectively. Higher concentrations of testosterone were observed at 18 months of age in crossbred males and at 24 months of age in indigenous males. These findings may explain the endocrinological support for comparatively late sexual maturity in indigenous males.